2006
DOI: 10.1111/j.1574-695x.2006.00054.x
|View full text |Cite
|
Sign up to set email alerts
|

New insight into the diagnosis of fastidious bacterial endocarditis

Abstract: Sterile blood cultures are noted in one third of patients with infectious endocarditis. Although in half of cases this is due to previous antibiotic therapy, in the other half, the aetiology of culture-negative endocarditis is intracellular bacteria such as Coxiella burnetii or fastidious growing bacteria. Although it was previously considered that the prevalence of such organisms was identical throughout the world, recent investigations on Bartonella endocarditis clearly showed that the aetiology of culture-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
71
2
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 66 publications
2
71
2
3
Order By: Relevance
“…arupensis (11), Bartonella koehlerae (12), Bartonella alsatica (13,14), and "Candidatus Bartonella mayotimonensis" (15), have occasionally been reported in the literature. Epidemiological data suggest a European-African gradient distribution in the prevalence of Bartonella endocarditis, the highest prevalence being reported in southern countries (7). In Europe, the prevalence of Bartonella endocarditis among those with infective endocarditis is 0% in Sweden, 1.1% in the United Kingdom, and 3% in France and Germany (7), and it reaches 15.6% and 9.8% in Algeria (16) and Tunisia (17), respectively.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…arupensis (11), Bartonella koehlerae (12), Bartonella alsatica (13,14), and "Candidatus Bartonella mayotimonensis" (15), have occasionally been reported in the literature. Epidemiological data suggest a European-African gradient distribution in the prevalence of Bartonella endocarditis, the highest prevalence being reported in southern countries (7). In Europe, the prevalence of Bartonella endocarditis among those with infective endocarditis is 0% in Sweden, 1.1% in the United Kingdom, and 3% in France and Germany (7), and it reaches 15.6% and 9.8% in Algeria (16) and Tunisia (17), respectively.…”
mentioning
confidence: 99%
“…Bartonella species were first recognized as endocarditis agents in 1993 when 3 such cases were reported (3)(4)(5). After the seminal work of Drancourt et al (6), 120 cases were reported in the literature until 2006 (7). Most reported cases were attributed to Bartonella quintana, the agent of trench fever that may also cause endocarditis, chronic bacteremia, and bacillary angiomatosis, and Bartonella henselae, which mainly causes cat scratch disease, endocarditis, bacillary angiomatosis, peliosis hepatis, and osteomyelitis (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Blood culture negative endocarditis (BCNE) represents a well-known clinical problem occurring in large range of patients (2.5 -31%) among IE cases (7,8,16,17). Blood sampling after previous antibiotic treatment, and/or the presence of fastidious microorgan-isms (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Gram negative bacilli belonging to HACEK group, nutritionally deficient streptococci, intracellular bacteria) are listed among the causes of blood culture negative cases. An important amount of BCNE may be due to Q fever endocarditis, determined by a chronic infection with Coxiella burnetii (16).…”
Section: Introductionmentioning
confidence: 99%